59. The temporal pole is implicated in migraine pathophysiology: Evidence from a transcranial direct current stimulation study. Issue 12 (December 2017) - Cortese, F.; Coppola, G.; Bove, I.; Parisi, V.; Pierelli, F.
Abstract : Neuroimaging studies have implicated the temporal pole (TP) in migraine pathophysiology. Here, we aim to verify whether the enhancement of TP excitability by means of anodal transcranial direct current stimulation (tDCS) may change the interictal abnormal multimodal sensory processing in migraine. Thirty-two interictal migraineurs underwent visual (VEPs, 600 sweeps, 3.1 Hz, 15 min of arc check) and median nerve somatosensory (SSEPs, 200 sweeps, 4.4 Hz) evoked potentials before and immediately after 20-min anodal ( N = 16) or sham ( N = 16) tDCS delivered over the left TP (2 mA, cathode placed on the right arm). We measured VEPs N1-P1 and SSEPs N20-P25 amplitude habituations. Before tDCS or sham, migraine patients lacked habituation in response to both visual (+0.09, +0.05 respectively in the tDCS and sham group) and somatosensory (+0.5, +0.2) repetitive stimulations. After anodal tDCS but not sham stimulation, migraine patients showed normalization of the interictal habituation deficit in response to visual (−0.25, p = 0.01), but not to somatosensory (+0.3) repetitive stimulations. This distinct cortical finding in response to tDCS could be related to the fact that the temporal pole belongs to the so-called ventral stream of the visual pathway.